A Comparative Study on Legal Protection for Consumers Using Digital Lending Services in Indonesia and Singapore from the Perspective of Legal Development Theory: Perbandingan Perlindungan Hukum bagi Konsumen Pengguna Layanan Pendanaan Digital antara Indonesia dan Singapura dalam Perspektif Teori Pembangunan Hukum - Febrianto, Rizky; Gunadi, Ariawan (Rechtsidee, 2025)
General Background: The rapid expansion of digital lending in Indonesia and Singapore reflects a broader transformation in financial technology that demands stronger regulatory safeguards. Specific Background: Despite regulatory efforts, Indonesia continues to face challenges of weak supervision, low industry compliance, and high exposure to illegal platforms, whereas Singapore has established a more structured and integrated regulatory model. Knowledge Gap: Comparative analyses examining both countries’ legal frameworks through the lens of Legal Development Theory remain limited, particularly regarding their effectiveness in ensuring consumer protection. Aims: This study analyzes and compares the legal protection mechanisms governing digital lending in Indonesia and Singapore while assessing their alignment with legal development principles. Results: Findings show Indonesia relies on POJK 40/2024, Consumer Protection Law, and Personal Data Protection Law, yet enforcement remains inconsistent; in contrast, Singapore’s Payment Services Act, CPFTA, PDPA, and MAS compliance-based supervision ensure stronger preventive regulation and more efficient dispute resolution. Novelty: This research integrates comparative regulatory analysis with Legal Development Theory to reveal differing developmental orientations of both jurisdictions. Implications: Strengthening supervisory capacity and enforcement is essential for Indonesia to build a safer, equitable, and innovation-supportive digital lending ecosystem. Highlights: Strong contrast exists between Indonesia’s fragmented enforcement and Singapore’s integrated MAS-led regulatory model. Singapore emphasizes preventive, risk-based oversight, while Indonesia remains largely reactive to emerging problems. Effective consumer protection hinges not only on regulation completeness but also on consistent supervision and institutional capacity. Keywords: Digital Lending, Consumer Protection, Fintech Regulation, Legal Development Theory, Comparative Law